Coronary Artery PET/MR Imaging: Feasibility, Limitations, and Solutions - Robson, Philip M. (JACC Cardiovasc Imaging, 2017)
OBJECTIVES: The aims of this study were to describe the authors’ initial experience with combined coronary artery positron emission tomographic (PET) and magnetic resonance (MR) imaging using (18)F-fluorodeoxyglucose ((18)F-FDG) and (18)F-sodium fluoride ((18)F-NaF) radiotracers, describe common problems and their solutions, and demonstrate the feasibility of coronary PET/MR imaging in appropriate patients. BACKGROUND: Recently, PET imaging has been applied to the aortic valve and regions of atherosclerosis. (18)F-FDG PET imaging has become established for imaging inflammation in atherosclerosis in the aorta and carotid arteries. Moreover, (18)F-NaF has emerged as a novel tracer of active microcalcification in the aortic valve and coronary arteries. Coronary PET imaging remains challenging because of the small caliber of the vessels and their complex motion. Currently, most coronary imaging uses combined PET and computed tomographic imaging, but there is increasing enthusiasm for PET/MR imaging because of its reduced radiation, potential to correct for motion, and the complementary information available from cardiac MR in a single scan. METHODS: Twenty-three patients with diagnosed or documented risk factors for coronary artery disease underwent either (18)F-FDG or (18)F-NaF PET/MR imaging. Standard breath-held MR-based attenuation correction was compared with a novel free-breathing approach. The impact on PET image artifacts and the interpretation of vascular uptake were evaluated semiquantitatively by expert readers. Moreover, PET reconstructions with more algorithm iterations were compared visually and by target-to-background ratio. RESULTS: Image quality was significantly improved by novel free-breathing attenuation correction. Moreover, conspicuity of coronary uptake was improved by increasing the number of algorithm iterations from 3 to 6. Elevated radiotracer uptake could be localized to individual coronary lesions using both (18)F-FDG (n = 1, maximal target-to-background ratio = 1.61) and (18)F-NaF (n = 7, maximal target-to-background ratio = 1.55 ± 0.37), including in 1 culprit plaque post–myocardial infarction confirmed by myocardial late gadolinium enhancement. CONCLUSIONS: The authors provide the first demonstration of successful, low-radiation (7.2 mSv) PET/MR imaging of inflammation and microcalcification activity in the coronary arteries. However, this requires specialized approaches tailored to coronary imaging for both attenuation correction and PET reconstruction.